The Legality of Interfaith Marriage in Salatiga: A Perspective from Structural Functional Theory and Sadd al-Dzari'ah - Al Amin, Rokhana Khalifah; Huda, Muhammad Chairul (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Interfaith marriages in Salatiga can be legally registered without requiring either partner to adhere to the other's religion. This study aims to describe the process by which interfaith couples obtain legal recognition for their marriages in Salatiga. The research employs a qualitative method with sociological and normative approaches. The analysis is conducted using Talcott Parsons' structural-functional theory and the ushul fiqh method of saddu al-żari’ah. The findings reveal that interfaith marriage processes in Salatiga proceed smoothly due to a well-organized social system. The AGIL functions (Adaptation, Goal Attainment, Integration, Latency) are fulfilled, such as the couples’ adaptation through dual marriage ceremonies according to their respective religions, goal attainment by obtaining legally recognized marriage documents, integration through collaboration between the Percik NGO, religious leaders, and the Civil Registry Office (Disdukcapil), and latency by maintaining consistent registration policies despite changes in leadership at the Civil Registry Office. The saddu al-żari’ah approach confirms that legalizing interfaith marriages yields positive impacts, including legal protection for couples and their children, as well as clear recognition of rights and obligations. Thus, the policy of interfaith marriage registration in Salatiga not only supports social justice but also aligns with Islamic legal principles.